ANALISA DAMPAK EKONOMI BANK SAMPAH MASYARAKAT TERHADAP PENINGKATAN KUALITAS HIDUP MASYARAKAT DI KOTA MALANG - Rukayah (Bappeda Kota Malang, 2019)
The existence of a Waste Bank as one of the manifestations of a Waste Bank management program is very possible to have an impact on improving accessibility to increasing community income. The purpose of this study is to identify the impact of waste banks that can be felt by the community and the surrounding environment in each sub-district in the city of Malang, mapping membership data in each sub-district with data characteristics grouped according to participant status and activity of participants. To prove the hypothesis that has been put forward, then in this study used quantitative analysis method, namely simple linear regression analysis. From the results of the analysis, it is known that the existence of BSM Malang City also influences the improvement of the family economy, but there has been no impact in the long term and multipliereffect. This is due to the uncertainty of the customer's income, as well as the results of savings and loans that are only used for daily needs and during holidays.